1970
DOI: 10.3329/bjb.v37i2.1713
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and anatomy of three subsp. of Crocus speciosus Bieb.

Abstract: Moprhology and anatomy of Crocus speciosus Bieb. subsp. speciosus, C. speciosus Bieb. subsp. ilgazensis, C. speciosus subsp. xantholaimos were done. Two of them (subsp. ilgazensis and xantholaimos) are endemic to small areas of Turkey. The subsp. xantholaimos has flowers with tube stained yellow. The subsp. ilgazensis has a corm splitting into vertical fibres. These properties are characteristic for the two subspecies investigated. Cross-sections of root and aerial stem of three subspecies were examined and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Дослідження будови листків видів Crocus були проведені деякими вченими, але лише для середземноморських видів (Шорина, 1975;Özdemir, Kilinc, 2008;Sanei, Rahimyan, 2006;Satil, Selvi, 2007). Для видів Crocus флори України такі детальні дослідження проведені вперше.…”
Section: результати досліджень та обговоренняunclassified
“…Дослідження будови листків видів Crocus були проведені деякими вченими, але лише для середземноморських видів (Шорина, 1975;Özdemir, Kilinc, 2008;Sanei, Rahimyan, 2006;Satil, Selvi, 2007). Для видів Crocus флори України такі детальні дослідження проведені вперше.…”
Section: результати досліджень та обговоренняunclassified
“…In recent years, several studies were focused on classification of different genus of Crocus (GRILLI CIOLA et al, 2004;ÖZDEMIR et al, 2008;BAGHALIAN et al, 2010), but few of them included the differences between various accessions of cultivated saffron. BAGHALIAN et al (2010) have confirmed necessary of research on genetic variation and heritability of agro-morphological and phytochemical traits of this crop.…”
Section: Morphological Analysismentioning
confidence: 99%
“…Study of plant genetic diversity is a prerequisite of each breeding program (HADIAN et al, 2008). For this purpose, different morphological, molecular, physiological and phytochemical methods have been tested to reveal relationships among different species of plants (ÖZDEMIR et al, 2008;OKASAKA et al, 2009;IKINCI et al, 2010). So far, several researchers have attempted to study morphological, molecular and phytochemical characters of saffron germplasm in different countries (GRILLI CIOLA et al, 2001;PARDO et al, 2004;ZUBER et al, 2004;SOHEILIVAND et al, 2007;GRESTA et al, 2009;RUBIO-MORAGA et al, 2009;BAGHALIAN et al, 2010;FERNANDEZ et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The plant originated from Greece, Turkey and Iran, but is already widely cultivated in various European countries [20]. The corms and leaves of this Crocus species in Turkey are used for food [21].…”
Section: Introductionmentioning
confidence: 99%
“…Leaves of C. speciosus appear after flowering. Leaves a hysteranthous, until 20 mm long, green with a distinct mid-white stripe [20,21]. Due to the fact that there are no data in the literature on the chemical composition of leaves of this Crocus species, this study focused on the analysis of phenolic compounds of the chosen raw material.…”
Section: Introductionmentioning
confidence: 99%